Probiotic Lactobacillus strains protect against myelosuppression and immunosuppression in cyclophosphamide-treated mice - Salva, Maria Susana (2014)
This work evaluated the capacity of two probiotic strains, Lactobacillus casei CRL431 and Lactobacillus rhamnosus CRL1506, to protect against myelosuppression and immunosuppression in cyclophosphamide (Cy)-treated mice. Changes inmature granulocytes and progenitor cells in bonemarrow (BM) and blood were studied. In addition, the ability of probiotics to accelerate the recovery of the immune response against the opportunistic pathogen Candida albicans was evaluated.We demonstrated for the first time that the preventive treatmentwith immunomodulatory lactobacilli such as L. casei CRL431 or L. rhamnosus CRL1506 was able to increase immature myeloid progenitors in the BM, allowing an early recovery of myeloid cells after Cy administration. Probiotic lactobacilli were also capable to induce an early recovery of neutrophils in blood, improve phagocytic cells recruitment to infectious sites and increase the resistance against the opportunistic pathogen C. albicans. Although deeper studies regarding the cellular and molecularmechanisms of probiotic actions are needed, these findings support the idea that strains like CRL431 and CRL1506 may accelerate the recovery of Cy-caused immunosuppression by immunopotentiating myeloid cells. Then, probiotic lactobacilli have the potential to be used as alternatives for lessening chemotherapy-induced immunosuppression in cancer patients.